PEMANFAATAN SIMBIOSIS MIKROALGA Chlorella sp. DAN STARBACT® UNTUK MENURUNKAN KADAR POLUTAN LIMBAH CAIR SAGU - Fajar Restuhadi; Yelmira Zalfiatri; Dini Aji Pringgondani (Program Pascasarjana Universitas Riau, 2017)
The puspose of this research was to study the symbiotic system of a complex microorganisms contained in Starbact® as a decomposer agent with the addition of photosynthetic microoalgae Chlorella sp. as an oxygen producer in reducing organic loads of sago milling effluent. The experimental design was Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments were concentration variations of Starbact® (0, 0.135, 0.270, 0.405, and 0.540 per cent v/v, respectively) with 800 ml/L (6,6 x 106 cell/ml) microalgae Chlorella sp. added up with waste sago milling effluent into total of 2 liters of the liquid. The data obtained were analyzed statistically using Analiysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DNMRT) at 5% level. The result showed that the addition of Starbact microorganisms had significant affect for COD, BOD, TSS, Nitrate, Phospate, DO and pH. The treatment chosen from the result of this research was the P4 treatment showed the highest level of reduction which had the value of COD 88,04%, BOD of 85,27%, TSS of 71,67%, Phospate of 48,21%, Nitrate of 71,06%. The result also showed an increasing of DO as much as 3 times from 1.85 mg/L into 5.91 mg/L, while pH increased significantly from 4.1 into 7.4.